Emerging role for Ureaplasma parvum serovar 3: Active infection in women with silent high‐risk human papillomavirus and in women with idiopathic infertility. Issue 10 (18th March 2019) - Zanotta, Nunzia; Campisciano, Giuseppina; Morassut, Sara; Castro‐Silva, Eugenia; Luksa, Viviana; Zito, Gabriella; Luppi, Stefania; Martinelli, Monica; Colli, Claudia; De Seta, Francesco; Ricci, Giuseppe; Suligoi, Barbara; et al.
Abstract: Recently, there are controversial opinions on the presence of Mycoplasmas / Ureaplasmas as colonizers or pathogens, and on the use of a targeted therapy. This study aimed to characterize Mycoplasmas / Ureaplasmas infections in reproductive age women, including the acquisition of sexually transmitted (ST) pathogens and poor birth outcomes. A total of 646 healthy Italian women fulfilled the inclusion criteria including 521 infertile women, 65 pregnant women, and 60 fertile women with identified risk factors and symptomatic for vaginitis/cervicitis. Multiplex and quantitative molecular techniques and direct automatic DNA sequencing were performed to assess the genome structure of Mycoplasma/Ureaplasma species and ST infected pathogens. Ureaplasma parvum serovar 3 represented the predominant colonizer of the urogenital tract of this series and the unique species significantly associated with ST pathogens coinfection ( p  < 0.01). U. parvum load >10 4 bacteria/ml, suggestive of active infection, has been measured only in asymptomatic high‐risk human papillomavirus infected women (24.3%) and in 40% of women with idiopathic infertility. To note, 16% of the follicular fluid from these idiopathic women resulted infected with U. parvum . In conclusion, the present study focused the attention on U. parvum serovar 3 as emerging microorganism in sexually active women that may have the benefit of targeted therapy.